Newer Classification System for Fissured Tongue: An Epidemiological Approach - Ramachandran Sudarshan; G. Sree Vijayabala; Y. Samata; A. Ravikiran (Journal of Tropical Medicine)
Introduction. Fissured tongue is a commonly encountered tongue disorder in dental practice. But there is a lack of data on different pattern, severity, and association of fissuring with various systemic disorders and other tongue anomalies. This study attempts to establish a classification system for fissured tongue and to know the correlation with the systemic health and other disorders of the tongue. Materials and Methods. A total of 1000 subjects between the age groups of 10 and 80 years were included in the study. Pattern of fissuring, allied systemic diseases, and related tongue anomalies were tabulated. Results. Out of 1000 subjects, 387 subjects presented with fissured tongue. Out of 387 subjects, hypertension was present in 57 cases, 18 subjects had diabetes, and 3 subjects had both hypertension and diabetes. Central longitudinal type was found to be the most common type of tongue fissuring. Conclusion. Fissured tongue has been found to be associated with certain systemic disease and further researches are required to know positive correlation. If a correlation exists, such disorders could be diagnosed earlier by identifying fissured tongue at an earlier age.